Consider the function f given by f(x)=x*(e^(-x^2)) for all real numbers x.

Find the value of integral from 0 to infinity of [x*f(x)]dx given the fact that the integral from 0 to infinity of (e^(-x^2))dx = root pi / 2

Respuesta :

Answer:

[tex]\int^{\infty}_{0}xf(x)dx=\frac{\pi}{4}[/tex]  

Step-by-step explanation:

We need to find the integrate of:

[tex]\int^{\infty}_{0}xf(x)dx[/tex]

Let's use the integration by parts rule.

[tex]\int^{\infty}_{0}xf(x)dx=u*v-\int vdu[/tex] (1)

[tex]u=x[/tex] and [tex]du=dx[/tex]

[tex]dv=f(x)dx[/tex] and [tex]v=\int f(x)dx[/tex]

[tex]f(x)=xe^{-x^{2}}[/tex]

[tex]v=\int xe^{-x^{2}}dx[/tex] if we use change variable we can solve it, we can do [tex]a=-x^{2}[/tex] then [tex]da=-2xdx[/tex]

So we have:

[tex]v=-\frac{1}{2}\int e^{a}da[/tex]

[tex]v=-\frac{1}{2}e^{-x^{2}}[/tex]

Using this in (1) we have:

[tex]\int^{\infty}_{0}xf(x)dx=(-\frac{1}{2}x*e^{-x^{2}})|^{\infty}_{0}-\int^{\infty}_{0} (-\frac{1}{2}e^{-x^{2}})dx[/tex]

The used criteria to make the first term zero is because the exponential tends to zero faster than the x tends to infinity.    

[tex]\int^{\infty}_{0}xf(x)dx=0+\frac{1}{2}\int^{\infty}_{0} e^{-x^{2}}dx[/tex]  

We know that the integral from 0 to infinity of [tex]e^{-x^{2}}=\frac{\sqrt{\pi}}{2}[/tex], hence:  [tex]\int^{\infty}_{0}xf(x)dx=0+\frac{1}{2}\frac{\sqrt{\pi}}{2}[/tex]

[tex]\int^{\infty}_{0}xf(x)dx=\frac{\pi}{4}[/tex]  

I hope it helps you!

 

         

The definite integral of [tex]f(x) = x\cdot e^{-x^{2}}[/tex] from 0 to [tex]+\infty[/tex] is [tex]\frac{1}{2}[/tex].

How to integrate an expression including an improper expression

The integral given in statement can be solved by integration by substitution:

[tex]\int\limits^{+\infty}_{0} {x\cdot e^{-x^{2}}} \, dx = -\frac{1}{2} \int\limits^{+\infty}_{0} {e^{u}} \, du[/tex], where [tex]u = -x^{2}[/tex]    (1)

[tex]\int\limits^{+\infty}_{0} {x\cdot e^{-x^{2}}} \, dx = \frac{1}{2}\cdot e^{-x^{2}}|_{0}^{+\infty}[/tex]

We could notice that [tex]e^{-x^{2} } \to 0[/tex] when [tex]x \to + \infty[/tex]. Then, we have the following result:

[tex]\int\limits^{+\infty}_{0} {x\cdot e^{-x^{2}}} \, dx = \frac{1}{2}\cdot (1-0)[/tex]

[tex]\int\limits^{+\infty}_{0} {x\cdot e^{-x^{2}}} \, dx = \frac{1}{2}[/tex]

The definite integral of [tex]f(x) = x\cdot e^{-x^{2}}[/tex] from 0 to [tex]+\infty[/tex] is [tex]\frac{1}{2}[/tex]. [tex]\blacksquare[/tex]

To learn more on definite integrals, we kindly invite to check this verified question: https://brainly.com/question/22655212